Polybrominated diphenyl ethers with broad spectrum antibacterial activity from the Indonesian marine sponge Lamellodysidea herbacea - Novriyandi Hanif, Muhammad Syarqul Ardan ,Dudi Tohir, Andi Setiawan, Nicole J. de Voogd, Muhammad Farid, Anggia Murni, Junichi Tanaka (Journal of Applied Pharmaceutical Science, 2019)
The marine sponge Lamellodysidea herbacea is one of the marine organisms containing unique organobromine molecules polybrominated diphenyl ethers (PBDEs) which have diverse biological activities. Compounds 1−4 have been successfully isolated and their structures were elucidated using nuclear magnetic resonance (NMR) spectroscopy, single-crystal x-ray diffraction, and comparison with data in literature. Compound 1, C12H6O4Br6, was isolated in gram quantity (1.35 g) and elucidated as 2,3,4,5-tetrabromo-6-(3Ê¹,5Ê¹-dibromo-2Ê¹-hydroxyphenoxy)phenol after NMR and X-ray analysis. Compound 1 takes a twist-like conformation with torsion angle Ï•1 = 27.7 (6)°; Ï•2 = 86.5 (5)°, while the angle of the ether bond is 117.5°. Compounds 2−4 were elucidated as 2,3,5-tribromo-6-(3Ê¹,5Ê¹- dibromo-2Ê¹-hydroxyphenoxy)anisole, 2,3,5-tribromo-6-(3Ê¹,5Ê¹-dibromomethoxyphenoxy) phenol, 2,3,5-tribromo-6- (3Ê¹,5Ê¹-hydroxyphenoxy)phenol, respectively. Antibacterial evaluation of 1−4 on Gram-positive and Gram-negative pathogens showed that the potent activity was at 0.08 μg/disk, 12 ± 0 mm (Staphylococcus aureus ATCC 6538); 6.25 μg/disk, 10 ± 0 mm (Klebsiella pneumoniae); and 50 μg/disk, 12 ± 0 mm (ampicillin-resistant Escherichia coli). Compounds 1, 2, and 4 showed ichthyotoxicity (zebrafish embryos, Danio rerio) at a level of LC50 >10 μg/ml [dead, 48 hours postfertilization (hpf)]. This is the first report that compound 4 inhibits the growth of antibiotic-resistant bacteria.
Keywords: PBDE, Lamellodysidea herbacea, NMR, X-ray crystallography, antibiotic resistance.